1993
DOI: 10.1002/jctb.280560315
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical properties of the mixed solvent of 2‐piperidineethanol, sulfolane and water

Abstract: Abstract:The physicochemical properties of the mixed solvent of 2-piperidineethanol (2-PE), sulfolane (TMS) and water were determined over a wide range of temperatures and compositions. The density, the viscosity and the dissociation constant, as well as the solubility of N,O in this mixed solvent were correlated as a function of temperature and composition over the entire experimental range. The models are useful not only for the ternary solvent system, but also for the binary solvent systems, such as 2-PE+H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…An activator, e.g., piperazine (PZ), may also be blended with alkanolamine to produce an aqueous solvent system with improved carbon dioxide absorption rate relative to that of the aqueous solvent system with one alkanolamine. Some of such studies which looked into absorption of carbon dioxide in PZ-activated aqueous alkanolamine solutions are available in the literature [2][3][4][5][6][7][8][9][10][11][12]. Some studies have also demonstrated the benefits of absorbing carbon dioxide in solutions containing (PZ + H 2 O) solvent systems [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…An activator, e.g., piperazine (PZ), may also be blended with alkanolamine to produce an aqueous solvent system with improved carbon dioxide absorption rate relative to that of the aqueous solvent system with one alkanolamine. Some of such studies which looked into absorption of carbon dioxide in PZ-activated aqueous alkanolamine solutions are available in the literature [2][3][4][5][6][7][8][9][10][11][12]. Some studies have also demonstrated the benefits of absorbing carbon dioxide in solutions containing (PZ + H 2 O) solvent systems [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…However, PZ-activated aqueous alkanolamine solutions, i.e. (PZ + alkanolamine + H 2 O) have shown the combined benefits of the amine and the activator as recent studies report and some patents have claimed [1,[5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the advantages of absorption characteristics of both physical and chemical solvents, mixed solvents such as organic solvent-alkanolamine have been suggested for use in acid gas capture processes (Astarita et al, 1983). Due to its high absorption capacity for CO 2 and H 2 S, sulfolane was often used as a physical solvent in the mixed physical/chemical solvent processes (e.g., sulfinol process) for acid gas capture (Xu et al, 1993;Kohl and Nielsen, 1997). For organic solvent-alkanolamine systems, vapor-liquid equilibrium data of H 2 S and CO 2 in sulfolane + AMP + water (Roberts and Mather, 1988), in sulfolane + 2-PE + water (Jou et al, 1998), and in sulfolane + MDEA + water (MacGregor and Mather, 1991) have been studied.…”
Section: Introductionmentioning
confidence: 99%